Market power, social welfare, and efficiency in the Peruvian microfinance - (:unkn) unknown (Springer Nature BV, 2024)
This study quantifies the social welfare loss caused by market power in Peru’s regulated microfinance industry and analyzes its effect on microfinance institutions’ (MFIs) efficiency from 2003 to 2019. We estimate the efficiency-adjusted Lerner ...
Keywords: Microfinanzas; Bienestar social